Bulan Suro dalam Tradisi Jawa-Islam: Kajian Sinkretisme Astronomi, Tafsir Qur’ani, Antropologi Budaya, dan Mitologi Lokal - Nihayatur Rohmah; Ahmad Junaidi; Novi Fitia Maliha; Erick Nauval Hafidz Bustomi (Jurnal Antologi Hukum, 2026)
The month of Suro reflects a unique process of syncretism between astronomical elements, Qur’anic interpretation, Javanese anthropological dynamics, and local mythological narratives that shape religious and cultural meanings within Javanese society. This study analyzes the interaction among these disciplines to reveal the holistic dimensions of the Suro Month phenomenon. The analysis begins with an astronomical perspective that highlights the synchronization of the Hijri–Javanese calendar, in which lunar phases align with cosmic rhythms, integrated with interpretations of Qur’anic verses concerning sacred time-such as Q.S. At-Taubah: 36-which emphasize temporal sanctity as a form of divine revelation. This approach is further enriched by anthropology, which examines pilgrimage rituals, sunnah fasting, and artistic performances such as wayang kulit as expressions of Javanese-Islamic identity, as well as local mythology that elaborates ancestral narratives harmoniously integrated with Islamic doctrine. Astronomy explains the ritual transition periods resulting from the dual-calendar system, Qur’anic interpretation connects the Prophet’s migration (Hijrah) and the story of Noah with spiritual symbolism, while Javanese anthropology reveals local adaptations such as bubur suro as forms of cultural acculturation. This integrative synthesis produces a comprehensive understanding of the Month of Suro as a syncretic phenomenon that enriches local fiqh and Islamic cultural studies, while also offering relevance for the reinterpretation of Javanese traditions within the framework of contemporary Islamic law (sharia).